(untitled) (Journal of Hama University, 2019)
The problem that led to research in the topic of civil society organizations, are weak functionsDevelopment in states in need of social and economic developmentAnd politicalAnd political Support the option of a state of national democracy, which is based on the marks of citizenship, The problem of the overlap between civil society organizations and NGOs. The importance of research appear in Chapter science between the concepts of business development and symbiotic, anddemocracy procedural. The adoption of approach two are the methodology of descriptive analysis, and The product of comparative. The study has two sections: the first lesson the entrance of knowledge, the second lesson the entrance of the proceduralThe study has two sections: the first lesson the entrance of knowledge, the second lesson the entrance of the procedural.And the second lesson the concept of citizenship and dialogue. The results of the study: determining the position of civil society organizations between state and society. And Expand the concept of citizenship procedurally by the election of the National.